The new transformed Sine G family of distribution with inferences and application - Osi, Abdulhameed; Singh Raghav, Yasphal; Ahmad Sabo, Shamsuddeen; Zakariyya Musa, Ibrahim (Brazilian Journal of Biometrics, 2025)
This article introduces the New Transformed Sine G Family of distributions, which is a new probability distribution based on trigonometric transformation. It provides detailed derivations of the statistical properties associated with this distribution, such as the hazard function, survival function, inverse hazard, quantile function, moments, moment generating function, and the median. The parameter estimation of the model was conducted using the maximum likelihood method, and the performance of the estimation method was evaluated through Monte Carlo simulation. Furthermore, the applicability of the proposed distribution was demonstrated by analyzing two real datasets, where the model showed superior fit compared to existing distributions for these datasets.